The mechanics of robot grasping - Rimon, Elon; Burdick, Joel Wakeman (Cambridge : Cambridge University Press, 2019)
In this comprehensive textbook about robot grasping, readers will discover an integrated look at the major concepts and technical results in robot grasp mechanics. A large body of prior research, including key theories, graphical techniques, and insights on robot hand designs, is organized into a systematic review, using common notation and a common analytical framework. With introductory and advanced chapters that support senior undergraduate and graduate level robotics courses, this book provides a full introduction to robot grasping principles that are needed to model and analyze multi-finger robot grasps, and serves as a valuable reference for robotics students, researchers, and practicing robot engineers. Each chapter contains many worked-out examples, exercises with full solutions, and figures that highlight new concepts and help the reader master the use of the theories and equations presented.
Introduction and overview page -- Rigid-body configuration space -- Configuration space tangent and cotangent vectors -- Rigid body equilibrium grasps -- A catalog of equilibrium grasps -- Introduction to secure grasps -- First-order immobilizing grasps -- Second-order immobilizing grasps -- Minimal immobilizing grasps -- Multi-finger caging grasps -- Frictionless H and supported stances under gravity -- Wrench resistant grasps -- Grasp quality functions -- Hand supported stances under gravity, part I -- Hand supported stances under gravity, part II -- The kinematics and mechanics of grasping mechanisms -- Grasp manipulability -- Hand mechanism compliance.
Title from publisher's bibliographic system (viewed on 11 Oct 2019).
Keywords: Robot hands -- Textbooks; Mechanical movements -- Textbooks; Robotics -- Textbooks